Customer journey: Online versus offline in fashion industry - Tapadinhas, Raquel Filipa Duarte (2022)
Technological improvements are allowing the development of the customer experience both online and offline, and the purpose is to create a better experience. Nowadays, customers can decide to purchase products/ services in two different ways, i.e., online or offline. The online experience has been changing the way companies reach the customer, while in-store experience is the traditional way of purchasing. This study analyses the customer journey and the most important attributes when the customer wants to purchase a product and has to choose between the two channels in the fashion industry, in Portugal. It is important to understand why customers choose a channel instead of the other one, and if the combination of the two channels can improve customer experience. The fashion industry is very competitive; therefore it is necessary to constantly innovative and integrate both channels, with the use of technologies, such as virtual reality. In this industry, sensory elements are crucial, and it is necessary that these elements are also present in the online channel. Can the combination of online and offline channels be the best option for customers with the help of technology? Interviews were conducted and a qualitative analysis was carried out. The main findings indicate that sensory elements are essential when customers what to purchase a clothing item and that is one of the reasons that customers, in general, prefer to purchase offline. Moreover, using new technologies to bring the two channels together seems to be a good option.